Some special cases of propagation characteristics of an elliptical step-index fiber with a conducting helical winding on the core-cladding boundary - An analytical treatment - Kumar D.; Singh II O.N. (My University, 2025)
Some special cases of propagation characteristics of an elliptical step-index fiber with a conducting helical winding on the core-cladding boundary are investigated analytically. Our optical waveguide is doubly unconventional: (1) In the choice of elliptic cross section and (2) in the choice of helical conducting winding between the core and the cladding. The characteristic equation and the cutoff condition is obtained. We consider the two special cases with the pitch angle ψ = 0° and ψ = π/2 to get simpler characteristic equations which contain modified Mathieu functions and their derivatives. The functions are expressed in series of Bessel's and modified Bessel's functions. The cutoff conditions are obtained. Dispersion curves are also obtained. The pitch angle of the helix has no effect on modal cutoff condition.